2020
DOI: 10.3390/su12073051
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selected Factors on Separation Efficiency in a Pneumatic Conical Separator

Abstract: Pneumatic separation is one of the available methods for cleaning seed mixtures. Variously shaped seeds, including spherical (vetch), elongated (wheat), and pyramid-shaped seeds (buckwheat), were analyzed in this study. A seed mixture containing 80% of main crop seeds and 20% of other crop seeds imitating impurities was separated in a pneumatic separator with the shape of an inverted cone in a stream of air. The regression equations describing the separation efficiency of the main crop seeds and other crop see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The source material quality coming to the enterprise from agricultural producers is determined by the analysis results of the samples (Chernyakov et al, 2021;Choszcz et al, 2020;Konopka et al, 2017).…”
Section: List Of Enterprisesmentioning
confidence: 99%
“…The source material quality coming to the enterprise from agricultural producers is determined by the analysis results of the samples (Chernyakov et al, 2021;Choszcz et al, 2020;Konopka et al, 2017).…”
Section: List Of Enterprisesmentioning
confidence: 99%
“…The key to obtaining high-quality seeds for commercial grain, along with modern varieties and applied technologies for growing agricultural crops, is the immediate, without intermediate storage, postharvest processing of the grain heap coming from the combines with its division into fractions: seed, fodder and unused waste. Such separation of the grain heap at the earliest stage of processing is possible with the use of two-aspiration air-sieve grain cleaning machines implementing fractional cleaning technology [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Panasiewicz, et al [8] found that an increase in the moisture content of crushed lupine seeds significantly decreased the separation effectiveness, while an increase in air velocity increased the separation effectiveness. Choszcz, et al [9] identified the effect of factors such as air velocity, moisture and grain type on the separation efficiency of the pneumatic conical separator. In order to increase the test weight and reduce impurities from types of grain product, Crepon and Duyme [10] tested the efficiency of three different types of grain cleaner machine using different grain flow and aspiration rate.…”
Section: Introductionmentioning
confidence: 99%